Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Lama Kerja Sebagai Variabel Moderating Pada Pt Ampalu Indah Lestari - Fina Hermalina; Vivi Nila Sari; Rahmat Wahyudi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of motivation and job satisfaction on employee performance with length of service as a moderating variable at PT Ampalu Indah Lestari. The data collection method was through surveys and distributing questionnaires, with a sample of 55 respondents. The analysis method used was structural equation modeling using smartpls. The results of this study showed a significant influence of motivation on employee performance. There was a significant influence of job satisfaction on employee performance. There was an insignificant influence of motivation on employee performance in moderation of length of service. There was an insignificant influence of job satisfaction on employee performance in moderation of length of service.